Patterns and Predictors of Health Behaviors among Racially/Ethnically Diverse Residents of Low-Income Housing Developments. Issue 1 (September 2014) - Harley, Amy E.; Yang, May; Stoddard, Anne M.; Adamkiewicz, Gary; Walker, Renee; Tucker-Seeley, Reginald D.; Allen, Jennifer D.; Sorensen, Glorian
Purpose: To examine behavioral patterns and sociodemographic predictors of diet, inactivity, and tobacco use among a diverse sample of residents from low-income housing developments. Design: In this cross-sectional survey study, households and residents were randomly selected using multistage cluster sampling. Setting: The study was conducted in 20 low-income housing developments in the Boston, Massachusetts, metropolitan area. Subjects: Subjects were 828 residents who completed the survey (response rate = 49.3%). Forty-one percent of participants were Hispanic and 38% were non-Hispanic Black. Measures: Outcomes measured were diet, inactivity, and tobacco use. Predictors measured were age, race/ethnicity, gender, education, country in which the subject was born, language spoken, and financial hardship. Analysis: Logistic regression analyses were conducted to examine the association of three health behaviors with sociodemographic factors. Results: Age, gender, language spoken, and financial hardship showed significant relationships with all three behaviors. For example, those who reported less financial hardship (odds ratio [OR] = 1.75) were more likely to eat healthier. Residents who spoke no English, or at least one language in addition to English, were significantly more likely to report healthier eating (OR = 2.78 and 3.30, respectively) than those who spoke English only. Men were significantly more likely to report less healthy eating (OR = 0.65) than were women. Similar trends emerged for inactivity and tobacco use. Conclusion: Effective health promotion interventions in low-income housing developments that leverage protective factors while addressing risk factors have the potential to reduce income-related health disparities in these concentrated resource-deprived neighborhoods.